Phonetic entrainment in L2 human-robot interaction: an investigation of children with and without autism spectrum disorder - Hong, Yitian; Chen, Si; Zhou, Fang; Chan, Angel; Tang, Tempo (Frontiers in Psychology, 2023)
Phonetic entrainment is a phenomenon in which people adjust their phonetic features to approach those of their conversation partner. Individuals with Autism Spectrum Disorder (ASD) have been reported to show some deficits in entrainment during their interactions with human interlocutors, though deficits in terms of significant differences from typically developing (TD) controls were not always registered. One reason related to the inconsistencies of whether deficits are detected or not in ASD is that the conversation partner’s speech could hardly be controlled, and both the participants and the partners might be adjusting their phonetic features. The variabilities in the speech of conversation partners and various social traits exhibited might make the phonetic entrainment (if any) of the participants less detectable. In this study, we attempted to reduce the variability of the interlocutors by employing a social robot and having it do a goal-directed conversation task with children with and without ASD. Fourteen children with ASD and twelve TD children participated. Results showed that ASD children showed comparable vowel formants and mean fundamental frequency (f0) entrainment as their TD peers, but they did not entrain their f0 range as the TD group did. These findings suggest that these children with ASD were able to show TD-like phonetic entrainment behaviors in vowel formants and f0 in a less complex situation, when the speech features and social traits of the interlocutor were controlled to facilitate phonetic entrainment in ASD children, and that the use of a social robot might have increased these children’s interests for phonetic entrainment. On the other hand, entrainment of f0 range was more challenging for these ASD children even in a more controlled situation. This study demonstrates the viability and potential of using human-robot interactions as a novel method to evaluate abilities and deficits in phonetic entrainment in children with ASD.